2009
DOI: 10.1021/jf902213w
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Antimicrobial Membranes: Coextrusion of Poly(lactic acid) and Nisaplin in the Presence of Plasticizers

Abstract: Nisin is a naturally occurring antimicrobial polypeptide and is popularly used in the food and food-packaging industries. Nisin is deactivated at temperatures higher than 120 degrees C and, therefore, cannot be directly incorporated into poly(L-lactic acid) (PLA), a biomass-derived biodegradable polymer, by coextrusion because PLA melts at temperatures around 160 degrees C or above. However, PLA can remain in a melt state at temperatures below the T(m) in the presence of lactic acid or other plasticizers. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 26 publications
(30 reference statements)
1
44
0
Order By: Relevance
“…The T g value for PLA and PLA-GR nanocomposites does not change significantly. This indicates that the reinforcement of GR in the PLA matrix does not lead to degradation of PLA by stimulating the formation of shorter chain segments [15,16].…”
Section: Resultsmentioning
confidence: 92%
“…The T g value for PLA and PLA-GR nanocomposites does not change significantly. This indicates that the reinforcement of GR in the PLA matrix does not lead to degradation of PLA by stimulating the formation of shorter chain segments [15,16].…”
Section: Resultsmentioning
confidence: 92%
“…The bacteria were activated by vaccination to MHB. The antimicrobial test was determined by method of Liu et al with some modification [30]. Bacteria constant temperature cultivation condition was 37°C and 18-24 h. A glass test tube containing testing specimens (0.18-0.20 g for each) was filled with 10 mL of broth.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Previous studies in our laboratory have demonstrated that antimicrobial films or coatings with U.S. Food and Drug Administration generally recognized as safe (GRAS) antimicrobials are effective in reducing pathogens in various foods (26,27,29,30,38,39). (29).…”
mentioning
confidence: 99%